The Socialization Of Patriotism In Jagoi Babang Sub-District - Zulfahita Zulfahita; Citra Utami; Fajar Wulandari; Fitri Fitri; Iip Istirahayu (STKIP Singkawang, 2019)
Indonesia is a country that has a variety of cultures, ethnicities, and races. This diversity is characteristic of the Indonesian state and the assets of the Indonesian people, in accordance with the motto of Unity in Diversity. Therefore, it is important for every citizen to have a sense of patriotism as a form of pride in the country of birth and shelter. The love of the motherland is not only implemented in the world of education, but also must be in the community, one of which is by conducting socialization to the community about the importance of the love of the motherland and then proceed with the screening of the Indonesian film titled